Targeting cyclin-dependent kinase 7—association between CDK7 and pMED1 expression in prostate cancer tissue. (5th May 2022) - Paulsen, Finn-Ole; Kang, Duan; Becker, Finn; Roth, Doris; Joerg, Vincent; Dreyer, Eva; Roesch, Marie C; Seidel, Christoph; Merseburger, Axel S; Kirfel, Jutta; Sailer, Verena; Offermann, Anne; et al.
Abstract: Cyclin-dependent kinase (CDK) 7-mediated phosphorylation of Mediator-complex subunit 1 (MED1) enhances androgen receptor (AR) activity in prostate cancer (PCa). Hyperactive AR-signalling plays a key role for the development of castration resistance. Several CDK7 inhibitors are currently under investigation in Phase I/II trials addressing solid tumours, including PCa. Aim of this study was to characterize the CDK7/phospho-(p)MED1 axis in human tissue. Immunohistochemistry was performed on 595 PCa samples including 394 primary tumour foci obtained by radical prostatectomy (RP), 64 advanced or recurrent tumours obtained by palliative transurethral resection of the prostate (pTUR), 65 lymph node metastases (LNM), 35 distant metastases (DM) and 36 benign samples. CDK7 is expressed in 79.3% of PCa tissues and protein levels are significantly higher in LNM, pTUR and DM and lower in benign tissues compared to primary tumours. CDK7 and pMED1 expression show strong positive correlation. High expression of CDK7 associated with shorter 5-year biochemical recurrence-free-survival (63.0% vs. 85.0%) and reduced survival persists when adjusted for T-Stage, nodal status, resection boundaries, grade group and pre-operative prostate-specific antigen in multivariate Cox-regression (hazard ratio 4.30; 95% CI, 1.43 to 12, 40, P = 0.007). High CDK7 and pMED1 levels correlate with nuclear AR expression. CDK7 positive tumours harbour higher Ki67 expression indices and show more frequently positive ERG (ETS-related gene)-status. In conclusion, CDK7 is frequently expressed in human PCa and predicts disease recurrence after RP. Therapeutical inhibition of CDK7 might be a promising approach in treatment of advanced PCa. Abstract : We conducted a comprehensive analysis of CDK7 expression in a large cohort of human prostate cancer tissues to investigate the CDK7/MED1/AR signalling axis. CDK7 predicts disease recurrence and is a promising target for treatment of advanced prostate cancer. Graphical Abstract: